Braking Energy Saving Technology of Train Based on Super Capacitor Energy Storage - LIU Guanghuan; LIU Lan; CHEN Guangzan; YIN Weiheng (Kongzhi Yu Xinxi Jishu)
Currently, methods such as resistor energy dissipation and inverter feedback are commonly adopted to consume or use the train braking energy in domestic rail transit system. Resistance energy consumption causes the energy waste, and inverter feedback energy must feedback to power grid in real time, in which the flexibility of time and power has a certain impact on the stability of grid when the grid load is not large. Based on the research and analysis of urban rail traction power supply system, it put forward a structure of capacitive energy absorption, established the mathematical model and calculation condition of the super capacitor energy storage device, and formed a relatively complete multi-control technology. The capacitive regenerative energy absorption and utilization scheme has been successfully applied to the Guangzhou Metro. It can not only store the energy generated by regenerative braking and, if necessary, but also feedback energy to the DC traction network, making full use of regenerative braking energy.